2020
DOI: 10.3390/electronics9122148
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Splitter Plate for Improving the Dielectric Recovery Strength of Low-Voltage Circuit Breaker

Abstract: The low-voltage circuit breakers are widely used to protect loads in the distribution system. Interruption reliability of circuit breakers is important because they are a protective device close to the customer. In particular, the re-ignition phenomenon leads to over-current blocking failure due to the arc re-formed between electrodes despite the normal trip of the circuit breaker. In this paper, in order to improve the interruption performance against re-ignition, the dielectric recovery voltage measurement s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…In other words, when the external temperature increases from 25 • C to 45 • C, it can be seen that both short-circuit characteristics and dielectric recovery strength deteriorate at a similar rate. This shows a similar tendency to the case of the experiment conducted previously by changing the thermal conductivity of the splitter plate [14]. The second external environmental condition is disturbing magnetic fields.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In other words, when the external temperature increases from 25 • C to 45 • C, it can be seen that both short-circuit characteristics and dielectric recovery strength deteriorate at a similar rate. This shows a similar tendency to the case of the experiment conducted previously by changing the thermal conductivity of the splitter plate [14]. The second external environmental condition is disturbing magnetic fields.…”
Section: Discussionsupporting
confidence: 83%
“…The previous paper confirmed the effect of the material of the splitter plate inside the arc extinguishment chamber on the dielectric recovery characteristics of the breaker [14]. In this test result, it was analyzed how the thermal conductivity of the material affects the dielectric recovery voltage through one-way ANOVA (Analysis of Variance) analysis [15].…”
Section: Temperaturementioning
confidence: 57%
See 1 more Smart Citation
“…[15]. In our precious research, the dielectric recovery strength according to materials of the splitter plate was studied and it was confirmed that the thermal conductivity of the material had a dominant effect on initial dielectric recovery [16].…”
Section: Introductionmentioning
confidence: 76%
“…A circuit model of a molded-case circuit breaker (MCCB) is proposed and the interruption phenomenon of the MCCB is analyzed in [7]. The dielectric recovery strength of a low-voltage MCCB is improved by changing the splitter plate [8]. An auxiliary solid-state switching device, along with a pre-charged commutation capacitor or a passive network, is used in a traditional solid-state DC breaker to force commutation in the primary solid-state switching device by reverse biasing [2].…”
Section: Introduction 1dc Network Development and Protection Solutionsmentioning
confidence: 99%